БОШЛАНҒИЧ СИНФ ЎҚУВЧИЛАРИНИНГ МАТННИ ЎҚИШ ВА ТУШУНИШ СИФАТИНИ PIRLS АСОСИДА БАҲОЛАШ УСУЛЛАРИ - Абдувалитов, Н. (SCIENCE and SOCIETY, 2020)
This article describes a case study of samples of world literature in reading lessons in elementary school, based on the program for the International Assessment of Text Reading and Understanding PIRLS. In particular, a sample of the PIRLS study assignment was used in a fourth-grade textbook to determine the level of understanding by students of Ch.Aitmatov’s fairy tale “Zhimzhiloq”.
Keywords: child’s personality; information sharing competence; reading culture; text; PIRLS assessment program; test tasks based on the PIRLS assessment program